1993
DOI: 10.1161/01.atv.13.6.777
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of thromboxane metabolites in healthy women after cessation of smoking.

Abstract: Cigarette smokers, but not former smokers, excrete more thromboxane A 2 (TxA 2 ) metabolites in the urine than do lifelong nonsmokers, which suggests chronic activation of their platelets. To further characterize the effect elicited by smoking on platelet function, we followed the change in urinary excretion of the 2,3-dinor (Tx-M) and 11-dehydro (dTx) metabolites of TxAj, analyzed by gas chromatography/mass spectrometry and radioimmunoassay, respectively, in eight healthy women who quit habitual smoking and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…It has been suggested that increased prostacyclin synthesis in smokers is a compensatory mechanism of healthy endothelium for the general vasoconstrictive properties of cigarette smoking (Lassila et al 1988), possibly by a mechanism mediated by some constituent(s) of tobacco smoke. Urinary excretion of 11-dehydro-TXB 2 was increased in smokers, which is in line with previous findings of increased systemic thromboxane synthesis in smokers (Nowak et al 1987;Lassila et al 1988;Wennmalm et al 1991;Rångemark et al 1993). Increased thromboxane synthesis reflects platelet activation (Nowak et al 1987).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It has been suggested that increased prostacyclin synthesis in smokers is a compensatory mechanism of healthy endothelium for the general vasoconstrictive properties of cigarette smoking (Lassila et al 1988), possibly by a mechanism mediated by some constituent(s) of tobacco smoke. Urinary excretion of 11-dehydro-TXB 2 was increased in smokers, which is in line with previous findings of increased systemic thromboxane synthesis in smokers (Nowak et al 1987;Lassila et al 1988;Wennmalm et al 1991;Rångemark et al 1993). Increased thromboxane synthesis reflects platelet activation (Nowak et al 1987).…”
Section: Discussionsupporting
confidence: 91%
“…Apparently healthy habitual smokers have increased systemic aggregatory and vasoconstrictory thromboxane (TX) A 2 synthesis measured as urinary excretion of 11-dehydro- (Rångemark et al 1993) and 2,3-dinor-TXB 2 (Nowak et al 1987;Lassila et al 1988;Wennmalm et al 1991). There are only few studies on the effects of smoking on the lipoxygenase pathway in man.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation has been demonstrated between daily cigarette consumption as assessed by urinary cotinine determination and the urinary excretion of thromboxane A2 metabolites [71,95,98] but not with urinary excretion of prostacyclin metabolites. This observation can be explained by in vivo platelet activation [98].…”
Section: Monitoring Of Groups At Riskmentioning
confidence: 94%
“…The level of 11-dehTxB 2 has been reported to be higher in smokers than in nonsmokers (25). Switching from smoking cigarettes to transdermal nicotine patch (30) or smoking cessation leads to decreased urinary 11-dehTxB 2 excretion (31).…”
Section: Introductionmentioning
confidence: 99%